FUNCTIONAL AND SENSORY CHARACTERISTICS OF SOURSOP TISANE (ANNONA MURICATA L) IN VARIOUS TYPES OF SWEETENERS - Fabiola, Vonny; Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2025)
Functional drinks are drinks that not only provide benefits for the body, but can also be enjoyed well when consumed. One of the functional drinks that has a good reputation among the general public is tea. Tea is the most frequently consumed drink and is generally followed by the addition of sweeteners to enhance the flavor. Soursop leaf tea is known to have bioactive content that is beneficial for health. This study aims to determine the effect of several types of sweeteners added to the physicochemical and sensory characteristics of soursop leaf tea functional drinks. This study design used a Completely Randomized Design (CRD) with 1 factor, namely the type of sweetener with 1 level of treatment, namely 4 types of sweeteners (sucrose (F1), kelulut honey (F2), commercial honey (F3), and stevia (F4)) and 1 unsweetened control (F0) with 5 repetitions each so that there were 25 experimental units. The data obtained were analyzed using Analysis of Variance (ANOVA) and continued with the Honestly Significant Difference (HSD) test at the 5% level. Sensory data were conducted using descriptive scoring test and data were analyzed using Kruskal Wallis method. The average anti alpha amylase activity ranged from 45.41% to 62.25%. Antioxidant activity ranged from 52.86% to 64.04%. Total phenolics contained in the sample ranged from 146.33 mg GAE/g to 188.26 mg GAE/g. The pH of the sample ranged from 4.41 to 5.91. While the TPT of the sample ranged from 0.68°brix to 7.64°brix. The results also showed that the sensory attributes of the five types of samples had different characteristics. Soursop leaf tea drink using kelulut honey as a sweetener has the best functional characteristics (antioxidants and anti alpha amylase), but has a low overall acceptance rate.